Effectiveness of Depression-Suicidal Behaviour Gatekeeper Training among police officers in three European regions: Outcomes of the Optimising Suicide Prevention Programmes and Their Implementation in Europe (OSPI-Europe) study - Arensman, E (2016)
BACKGROUND: Gatekeeper training for community facilitators, to identify and respond to those at risk of suicide, forms an important part of multi-level community-based suicide prevention programmes. AIMS: This study examined the effects of gatekeeper training on attitudes, knowledge and confidence of police officers in dealing with persons at risk of suicide. METHODS: A total of 828 police officers across three European regions participated in a 4-hour training programme which addressed the epidemiology of depression and suicidal behaviour, symptoms of depression, warning signs and risk factors associated with suicidal behaviour, motivating help-seeking behaviour, dealing with acute suicidal crisis and informing bereaved relatives. Participants completed internationally validated questionnaires assessing stigmatising attitudes, knowledge about depression and confidence in dealing with suicidal persons pre- and post-training. RESULTS: There were significant differences among countries in terms of previous exposure to suicidal persons and extent of previous training. Post-training evaluation demonstrated significant improvements in stigmatising attitudes, knowledge and confidence in all three countries. CONCLUSION: The consistently positive effects of gatekeeper training of police officers across different regions support inclusion of this type of training as a fundamental part of multi-level community-based suicide prevention programmes and roll-out, nationally and internationally.